Pengaruh Implementasi Website Pembelajaran Terhadap Hasil Belajar IPAS pada Peserta Didik Sekolah Dasar - Khairani, Fadhilah; Safinatunnajah, Salma; Oktaria, Oktaria; Syafrudin, Ulwan (Faculty of Teacher Training and Education, Musamus University, 2024)
Learning media has an important role in the process of delivering subject matter by educators. This research focuses on the problem of low student learning outcomes in IPAS subjects. The purpose of this study was to analyze the effect of learning website implementation on IPAS learning outcomes. The type of research is quantitative research with experimental research methods. The research design used is a non-equivalent control group design that uses experimental classes and control classes with a population of 35 and a sample of 17 students. The data collection technique used was the test technique. The data analysis technique was carried out with the n-gain test. The n-gain test results in the experimental class showed a mean value = 0.5164 and in the control class the mean value = 0.3109. The percentage of completeness (score ≥ 70) in the experimental class is higher than the control class, namely 70.5%> 33.3%, meaning that the implementation of the learning website on student learning outcomes in IPAS subjects in the experimental class is more effective than the use of visual learning media in the control class. There is a significant effect of learning website implementation on IPAS learning outcomes in grade V elementary school students.